2013
DOI: 10.2147/opth.s38543
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the indications and outcomes of capsular tension ring insertion during cataract surgery at a tertiary teaching hospital

Abstract: BackgroundThe purpose was to determine preoperative indications, intraoperative procedures, and outcomes of capsular tension ring (CTR) insertion during cataract surgery.MethodsA review of all patients undergoing cataract surgery with insertion of a CTR between July 2000 and June 2010 was conducted at The Royal Victorian Eye and Ear Hospital, a large tertiary teaching hospital in Victoria, Australia. Information relating to each patient’s demographic details, preoperative assessment, surgical procedure, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…Early studies have shown that CTR can improve capsular stability and maintain postoperative IOL centration in the setting of mild zonular weakness,11 12 as demonstrated in the present study in which IOLs were well centred in five of seven eyes (71.4%). However, CTR does not work well in the setting of seriously impaired zonules in spherophakia, whereas scleral-fixated IOL is an optimal alternative.…”
Section: Discussionsupporting
confidence: 70%
“…Early studies have shown that CTR can improve capsular stability and maintain postoperative IOL centration in the setting of mild zonular weakness,11 12 as demonstrated in the present study in which IOLs were well centred in five of seven eyes (71.4%). However, CTR does not work well in the setting of seriously impaired zonules in spherophakia, whereas scleral-fixated IOL is an optimal alternative.…”
Section: Discussionsupporting
confidence: 70%
“…Limited knowledge exists about the visual outcomes of cataract surgery involving CTRs. One Australian study of 84 eyes in which CTRs were inserted intraoperatively reported that compared to the preoperative VA, 73% had a better postoperative VA, 20% remained unchanged and 7% had worse postoperative VA (Wang et al 2013). The Australian study did not report comparative data on eyes without CTR insertion intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…A small pupil, intraoperative floppy iris syndrome (IFIS), a white cataract with no visible red reflex, zonular weakness and an instable capsular bag are difficulties that can be identified. Previous studies and clinical experience have shown that a small pupil or IFIS (Chang & Campbell 2005;Vollman et al 2014;Hashemi et al 2015;Ratra & Lam 2015), absence of a red reflex due to a white cataract (Jacob et al 2002) or an unstable capsular bag (Hasanee et al 2006;Blecher & Kirk 2008;Wang et al 2013;Weber & Cionni 2015) intraoperatively increase the risk of tissue damage and resultant complications. Adjunct devices such as capsular tension rings (CTRs), devices for mechanical stretching of the pupil and ophthalmic viscosurgical devices, trypan blue dye and capsular hooks are used in these challenging cases to improve the surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Wang et al. ), but reports on the postoperative outcome of CTR implantation in PEX eyes are scarce. Although we cannot extrapolate from our data, it is possible that CTR implantation may have a potential positive role in the intraocular management of zonular issues in eyes with PEX and may enhance safety of cortex removal, as CTR implantation was used in eyes with more extensive zonular weakness than in those eyes that did not receive a CTR.…”
Section: Discussionmentioning
confidence: 99%